THE BANKRUPTCY OF PERSONAL GUARATOR’S HEIRS UNDER INDONESIA LEGAL SYSTEM - Nuruzzhahrah Diza; Imas Rosidawati Wiradirja (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
The great advance of today’s business is certainly supported by the existence of banks loan facility. However, banks will not easily grant the loans to just anybody since there would be a probability that banks meet with the default risk. To reduce the impact of the risk, they require a guarantee. For banks, the guarantee shall legally provide them a protection, security and certainty in getting their loan repayment. As a common form, banks usually ask for property as collateral, but sometimes banks meet difficulty to execute it. Hence, nowadays, the banks will also ask for a personal guarantee. Personal guarantee is an agreement in which a third party agrees to fulfill the obligation of the debtor if debtor himself fail to do so. The personal guarantor has big responsibilities, even into the realm of bankruptcy. Even though a personal guarantor is not a debtor, a creditor may file him a bankruptcy petition to the Commercial Court if he meets the bankruptcy requirement. Problems then arise when a personal guarantor dies and it causes the creditors to lose a person who guarantees the debtor’s obligation. This research tackles with the problems by using a normative juridical approach with descriptive analysis of secondary data which consist of primary law materials and secondary law materials. The study shows that the death of personal guarantor causes the rights and obligations of personal guarantor upon the agreement are passed to his heirs. Consequently, his heirs as the party who do not involve in the loan agreement and the personal guarantee agreement may be filed the bankruptcy petition by the creditor as it is usually filed to the personal guarantor.